The Contribution of Sesotho Literature Books Read in Lesotho Secondary Schools in Perpetuating and Reinforcing Gender Stereotypes - Mochekele, Mapulane; Matsie, Nthama (Journal of Education and Practice, 2024)
Purpose: The overarching purpose of this research was to investigate the presence of gender stereotypes in the books used for teaching of Sesotho Literature in Lesotho secondary schools with a view towards recommending corrective interventions to the challenge. The study examined how physical attributes, character traits, gender roles within households and communities, and occupational roles were assigned to males and females in these books. Additionally, the research explored the power dynamics between male and female genders as depicted in these books. These categories served as the basis for coding and analysing the data. The study selected a purposive sample of four literary genres namely novels, dramas, poetry, and short stories. Methodology: Given the nature of the study, qualitative deductive content analysis was employed to gather and analyse the data from the chapters, stories, and poems within each of the genres. Findings: The findings indicated a significant prevalence of culturally constructed gender stereotypes within the examined works. The most important finding was that literature books perpetuate negative stereotypes which makes education a key contributor to some of the gender related problems. Unique contribution to theory, policy and practice: This research contributes to promotion of gender parity, reduction of gender-based violence and homicides which are problems ravaging the nation today.